An Implication of Geopolitics on Nepal’s Foreign Policy and National Security (Journal of Political Science, 2025)
This paper analyzes Nepal's geopolitical position between India and China, using a descriptive and analytical approach, using secondary data to explore its complex landscape and its implications for foreign policy and national security. Historically, Nepal has served as a buffer state, shaping its foreign policy and security strategies. However, as global dynamics have changed, so Nepal's perception of its role has evolved. The traditional idea of a buffer state is now giving away to more a proactive approach, with Nepal aiming to be a "bridge" between its neighbours fostering connectivity and cooperation. The shift is clear in Nepal's transition from viewing its landlocked as a drawback to embracing the potential of being a "land link," a crucial pathway for regional trade and connectivity. The evolving geopolitical landscape in South Asia, marked by increased competition between the United States and China, presents challenges and opportunities for Nepal. Nepal can achieve economic growth, regional cooperation, and infrastructural development by adopting a balanced and inclusive approach and cultivating strong relationships with all stakeholders. In conclusion, reshaping and implementing a pragmatic foreign policy and national security strategy based on the changing context is the best approach. With wisdom and foresight, Nepal can develop leverage through its unique geographical location.